Makna Keterlibatan Masyarakat Muslim dalam Ritual Hindu di Desa Angantiga, Petang, Kabupaten Badung - I Gst Pt Bagus Suka Arjawa (Pusat Kajian Bali Universitas Udayana, 2021)
Social harmony is a necessary condition for creating social stability in a plural society. Social stability will encourage the emergence of positive social interactions. This study examines the involvement of the Muslim community in participating in Hindu community rituals. This type of research is qualitative with the hermeneutic and verstehen methods. The theory used is symbolic and structural functional interactionism by developing the concepts of tolerance, solidarity and social harmony. The findings in the field are that the involvement of the Muslim community in the rituals of odalan (temple festival), cremation and mapag toya (welcoming the flowing of water) are form of social awareness of their existence in an area that shares the goal of social stability. To achieve this they develop a tolerant attitude and then manifest solidarity in their activities. From this understanding emerges social stability which shows social harmony in the region.